1999
DOI: 10.1017/s0029665199001305
|View full text |Cite
|
Sign up to set email alerts
|

Tracers to investigate protein and amino acid metabolism in human subjects

Abstract: Abbreviations: FSR, fractional synthesis rate; IRMS, isotope-ratio mass spectrometry; α-KIC, α-ketoisocaproic acid; MS, mass spectrometry; nb, net balance of tracer; NB, net balance of tracee; Ra, rate of appearance; Rd, rate of disappearance. The contribution of whole-body methods to the future gain of knowledge is expected to be limited due to the fact that most physiological disturbances have been investigated extensively, and due to the lack of information on the relative contribution of various tissues an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 73 publications
1
80
0
Order By: Relevance
“…In addition, the noninvasive study design precluded our ability to measure other potential biological effectors of protein metabolism such as circulating insulin, which can suppress whole body protein breakdown (Arslanian) and, provided there was a differential response between conditions, may have also contributed to the changes in WBPB observed herein. Nevertheless, other stable isotope methodologies are available to study whole body protein metabolism such as the primed constant [ 13 C]leucine infusion (45), which has been utilized successfully in research in children (13) and is arguably the current gold standard methodology (45). Despite the disadvantage of requiring repeated breath and blood samples that is not always feasible in children, the advantages of [ 13 C]leucine infusion include its preferential metabolism within skeletal muscle, the ability to measure changes in circulating amino acid and insulin concentrations, and the greater time resolution over which changes in protein turnover can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the noninvasive study design precluded our ability to measure other potential biological effectors of protein metabolism such as circulating insulin, which can suppress whole body protein breakdown (Arslanian) and, provided there was a differential response between conditions, may have also contributed to the changes in WBPB observed herein. Nevertheless, other stable isotope methodologies are available to study whole body protein metabolism such as the primed constant [ 13 C]leucine infusion (45), which has been utilized successfully in research in children (13) and is arguably the current gold standard methodology (45). Despite the disadvantage of requiring repeated breath and blood samples that is not always feasible in children, the advantages of [ 13 C]leucine infusion include its preferential metabolism within skeletal muscle, the ability to measure changes in circulating amino acid and insulin concentrations, and the greater time resolution over which changes in protein turnover can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids released from protein breakdown are either reutilised in protein synthesis or irreversibly lost via oxidation. Over the last two decades, isotope tracer methods such as leucine turnover technique have made it possible to accurately measure these components of whole-body protein metabolism by tracking the metabolic fate of a labelled amino acid (Wagenmakers 1999).…”
Section: Gh Effects On Protein Metabolismmentioning
confidence: 99%
“…To address the direct effects of GH on skeletal muscle protein turnover, investigators have measured the arterio-venous difference of labelled and unlabelled amino acids across the forearm or leg (Wagenmakers 1999). Using this technique, Fryburg et al (1991) and Fryburg & Barrett (1993) reported that GH induced an increase in protein synthesis without affecting the rate of protein breakdown in forearm muscles.…”
Section: Gh Effects On Protein Metabolismmentioning
confidence: 99%
“…GC-MS and IRMS are thus complementary techniques. Sometimes both are used in different parts of a tracer study, e.g., in total-body protein turnover determinations (Wagenmakers, 1999).…”
Section: Gas Chromatography-mass Spectrometry (Gc-ms)mentioning
confidence: 99%